Pro-inflammatory cytokines can act as intracellular modulators of commensal bacterial virulence. Issue 10 (October 2013) - Mahdavi, Jafar; Royer, Pierre-Joseph; Sjölinder, Hong S.; Azimi, Sheyda; Self, Tim; Stoof, Jeroen; Wheldon, Lee M.; Brännström, Kristoffer; Wilson, Raymond; Moreton, Joanna; Moir, James W. B.; Sihlbom, Carina; et al.
Abstract : Interactions between commensal pathogens and hosts are critical for disease development but the underlying mechanisms for switching between the commensal and virulent states are unknown. We show that the human pathogen Neisseria meningitidis, the leading cause of pyogenic meningitis, can modulate gene expression via uptake of host pro-inflammatory cytokines leading to increased virulence. This uptake is mediated by type IV pili (Tfp) and reliant on the PilT ATPase activity. Two Tfp subunits, PilE and PilQ, are identified as the ligands for TNF-α and IL-8 in a glycan-dependent manner, and their deletion results in decreased virulence and increased survival in a mouse model. We propose a novel mechanism by which pathogens use the twitching motility mode of the Tfp machinery for sensing and importing host elicitors, aligning with the inflamed environment and switching to the virulent state.